CYTOKINE PROFILE OF CHILDREN WITH ACUTE PYELONEPHRITIS - F. Kh. Irsalieva (American Journals, 2025)
Clinical and immunological examination of 26 children with acute pyelonephritis (P) was carried out. As a control, 17 healthy children of comparable age were examined. It was revealed that in children with OP there is a significant disbalance in the production of proinflammatory (IL-1B, IL-6, IL-8 and IL-18, respectively, in 16,1, in 3,5, in 12,6 and in 6,7 times. INF-y tends to decrease, and IN-a - a tendency to increase) and anti-inflammatory (IL-4 and IL-10 are increased by 3.0 and 2.9 times, respectively) of cytokines.
Keywords: Children, acute pyelonephritis, clinic, immunity, cytokines